Photoshop CS3 Extended video and 3D bible - Dayley, Lisa DaNae (Bible., 2008)
Harness the powerful new capabilities of Photoshop CS3 Extended When you think of editing 3D images, if your first thought isn't Photoshop's filters, styles, and paint tools, think again. Now you can apply your Photoshop skills to 3D and video with Photoshop's new CS3 Extended and the in-depth instruction in this comprehensive guide. Want to create composites using 3D objects? Learn how to animate? Jazz up YouTube videos? From animation basics to blending video layers, this book has what you need to produce digital and 3D content like a pro. Get to know 3D formats, workspac.